Different Representations of the Solutions to the Cylindrical Nonlinear Schrödinger Equation - ., Quasi-rational solutions to the cylindrical nonlinear Schrödinger equation (CNLS) in terms of wronskians and Fredholm determinants of order depending on real parameters are given. We get multi-parametric families of quasi-rational solutions to the CNLS equation and we construct explicitly solutions of order to (Discontinuity, Nonlinearity, and Complexity, 2026)
Quasi-rational solutions to the cylindrical nonlinear Schrödinger equation (CNLS) in terms of wronskians and Fredholm determinants of order $2N$ depending on $2N-2$ real parameters are given. We get multi-parametric families of quasi-rational solutions to the CNLS equation and we construct explicitly solutions of order $1$ to $5$.